Conducting multilevel studies in purchasing and supply management research. Issue 4 (October 2018) - Meschnig, Gavin; Carter, Craig; Kaufmann, Lutz
Abstract: Purchasing and supply management (PSM) research commonly covers multiple levels of theory and analysis. The theorizing and simultaneous testing of hypotheses across multiple levels is referred to as multilevel analysis (MLA) and is commonly performed using hierarchical linear modeling (HLM). Researchers in the PSM domain have paid little attention thus far to the topic of multilevel studies. Although MLA holds the potential to yield novel insights into PSM issues, it also generates new challenges for authors and reviewers alike. We contribute to this methodological dialogue by examining reasons for conducting multilevel PSM research and offering practical guidance for increasing its methodological rigor.